Probiotics in food. important preventive factor in children allergy, or a controversial add-on? review of the literature - Glaza, Izabela; Pietkun, Katarzyna; Szadujkis-Szadurski, Rafał; Nowacka, Krystyna; Hagner-Derengowska, Magdalena; Nowacki, Maciej (Medical and Biological Sciences, 2012)
Currently, one of the most frequently discussed topics related to the problem of child allergy are food allergies. Statistical data on the number of children burdened with this type of allergy are divergent according to reports of the individual authors. But invariably publications and scientific reports point to the upward trend in the number of newly identified various forms of food allergy. According to the data (AAAAI), in the years of 1997-2007 the number of diagnoses in children under 18 years of age increased by 18%. The European Data included in the reports (EFA) also confirm a growing trend in this respect in the recent years. In addition to significant development of diagnostics and therapy of various forms of childhood food allergy attention has been drawn to factors that affect the development of a preventive of this disease. In this type of factors, probiotics are also included .